Inequities in Access to Tricuspid Valve Treatments - Colin M. Barker, MD; Lisa S. Kemp, PhD; Melissa Mancilla, MBA; Sarah Mollenkopf, MPH; Candace Gunnarsson, PhD; Michael Ryan, MS; Guy David, PhD (JACC: Advances)
Background: Opportunities to minimize inequities in accessing treatments for tricuspid regurgitation disease should be considered. Objective: The objective of this study was to explore how access to new tricuspid regurgitation technologies change when heart centers are restricted by payer coverage requirements. Methods: This case series study identified U.S. hospitals with a record of performing transcatheter aortic valve replacement, transcatheter edge-to-edge repair, and tricuspid and mitral valve procedures for the calendar year 2021. Population 65+ years of age and Area Deprivation Index (ADI), were identified by zip code. We created 10 scenarios based on low, medium, and high hospital volumes for combinations of transcatheter aortic valve replacement, transcatheter edge-to-edge repair, tricuspid and mitral valve procedures. Distance from a zip code to scenario eligible hospitals was determined; the closest hospital to a zip code was identified as the distance someone with tricuspid regurgitation would have to travel for care. Each scenario was modeled with the dependent variable as the distance to the nearest scenario eligible hospital by ADI, controlling for population size 65+ years of age. Results: A total of 929 U.S. hospitals met our study inclusion. ADI was statistically significant in every scenario—when ADI goes up (more deprivation), distance to the nearest hospital increases. Patients in zip codes with low ADI travel an average of 15 to 52 miles, medium ADI 31 to 67 miles, and high ADI 47 to 95 miles. Conclusions: Patients in higher socioeconomic deprivation areas travel longer distances to hospitals meeting procedure volume requirements. Policymakers and patient advocacy groups should consider this to ensure equitable access to potentially life-saving technologies.